(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Objective: The purpose of this study is to estimate the serum level leptin and serotonin in adult men according to the characteristics of anthropometric measurements as well as to investigate its relationship with leptin and serotonin levels. Methods and procedures: This study included ninety-eight adult men volunteers, whose ages ranged between (20-50) years. The blood samples were taken between 8:30 and10:30 o’clock in morning. The ELISA kit has been used to assay the serum levels of leptin and serotonin hormones. The research population has been classified according to the anthropometric measurements, such as; the body mass index (BMI), the waist circumference (WC) and the percentage of body fat (BF%) which is calculated by a special formula. The results showed a significant increase (p<0.01) in the serum level of leptin hormone in obese groups in a comparison with the control groups, whereas there is a significant decreased (p<0.05) in the serum level of serotonin hormone in obese groups compared to the control groups. Furthermore, a significant negative correlation (p<0.03) between the serum leptin and serotonin is noticed. Conclusion: we concluded that there is a negative correlation between the serotonin (5- hydroxy tryptamine ,5-HT) hormone and obesity, for whenever the obesity increases, the level of the serotonin in the blood decreases. The leptin hormone, on the other hand, has a positive correlation with obesity. Therefore, the correlation between these two hormones is negative.